Comparative Pharmacognostic and Phytochemical Evaluation of Marketed and Wild-Collected Herbal Drugs: A Systematic Review - Newar, Arzoo; Dash, Biswajit; Kuumar, Pushpendra; Badola, Kritika; Trehan, Spardha; Goyal, Ankita; Asokan, Neethu (Journal of Neonatal Surgery, 2025)
Background: People worldwide use herbal medicines, but there are major differences in their quality depending on if they are wild-collected or available from the market, because of adulteration, environmental changes and processing. Such differences change their appearance, chemical properties and the potential of their therapeutic use. Objective: This study reviews the differences in Pharmacognostic and phytochemical characteristics between herbal drugs collected from wild versus market sources, with special attention to their quality and usefulness for treatment. Methods: For this study, reports were searched through PubMed, Scopus, Web of Science and Science Direct for studies published between 2000 and 2025. Relevant information on normalized measurements of macroscopic, microscopic, physicochemical and phytochemical factors was obtained and investigated. Results: Compared to wild herbal samples, herbal drugs marketed through firms usually had reduced taste, appearance and purity. Tests showed that commercial products contain less of certain bioactive chemicals and also showed inconsistent chromatographic patterns. The bioactivity of these microalgae such as their ability to combat oxidative damage and microbes, was also reduced. Conclusion: The research shows that the herbal industry must strongly enforce both Pharmacognostic and Phytochemical standardization. Combining old and new analytical tools is vital to confirm the safety, effectiveness and compliance of herbal medicines.